SOME ISSUES OF MODELING THE INTERACTION OF THE ECONOMY AND THE ENVIRONMENT - Sargsyan, Sona (Bulletin of Yerevan University G: Economics, 2020)
The article discusses the modeling of the interaction of the economy and the environment. Extended types of some classical models, taking into account environmental factors, are given. Balance, mixed, optimization models, and models of the circular economy, in particular, were analyzed. A model of a conflict game is presented where the conflicting parties are the economy and nature, and the interests of the players diverge. We analyzed the possibility of intergenerational equity and sustainability, based on the statistics of copper concentrate exports and the carbon intensity of GDP in the inclusive economic growth index of Armenia in 2018. Some directions of eco-restructuring and greening of production at the present stage of development of the Republic of Armenia are proposed
Keywords: economic growth, economic development, econology, environmental factor, economic-environmental models